Hexane fraction from the ethanolic extract of Sargassum serratifolium suppresses cell adhesion molecules via regulation of NF-κB and Nrf2 pathway in human umbilical vein endothelial cells - Wi-Gyeong Gwon; Sang-Gil Lee; Jae-Il Kim; Young-Mog Kim; Seon-Bong Kim; Hyeung-Rak Kim (Fisheries and Aquatic Sciences, 2019)
Abstract Sargassum serratifolium ethanolic extract has been known for strong antioxidant and anti-inflammatory properties. We prepared hexane fraction from the ethanolic extract of S. serratifolium (HSS) to improve biological activities. In this study, we investigated the effects of HSS on the inhibition of tumor necrosis factor (TNF)-α-induced monocyte adhesion to human umbilical vein endothelial cells (HUVECs). We found that HSS suppressed the production of cell adhesion molecules such as intracellular adhesion molecule-1 and vascular cell adhesion molecule-1 in TNF-α-induced HUVECs. Moreover, TNF-α-induced production of monocyte chemoattractant protein 1 and keratinocyte chemoattractant was inhibited by HSS treatment. HSS suppressed TNF-α-induced nuclear factor kappa B (NF-κB) activation via preventing proteolytic degradation of inhibitor κB-α. HSS induced the production of heme oxygenase 1 via translocation of Nrf2 into the nucleus in TNF-α-treated HUVECs. Overall, HSS alleviated vascular inflammation through the downregulation of NF-κB activation and the upregulation of Nrf2 activation in TNF-α-induced HUVECs. These results indicate that HSS may be used as therapeutic agents for vascular inflammatory disorders.